Study on formation and mechanical properties of rice husk/natural bentonite prepared composites - Farid Mulana (Syiah Kuala University, 2013)
In this study, composites were made from source of virgin HDPE and rice husk/natural bentonite as combined filler and mechanical properties of composites were measured. The purpose of study is to find the best condition of the ratio of rice husk/natural bentonite as matrix and the percentage of polyethylene-graft-maleic anhydride (MAPE) as coupling agent on quality of formed composites. In order to form these composites a hot press method was performed. The composite formation process was conducted at temperature of 170 oC for half hour. After pressed and heated then composites was cooled to room temperature and finally composites were tested to know its mechanical properties of tensile strength and bending strength. The results showed that addition of natural bentonite into matrix of rice husk have increased mechanical properties of composite compared to composites prepared by using only rice husk and virgin HDPE. Percentage of added MAPE also affect values of tensile and bending strength of composites. The effect of MAPE and natural bentonite which added during formation of composites caused the increasing adhesion bond between matrix and filler and as a result also increased the mechanicalproperties of composites. The highest tensile strength value of 18.2 MPa was found on composite with filler rice husk/natural bentonite ratio of 70:30 with addition of 5 wt% MAPE. While the highest bending strength value of 9.2 Mpa was obtained on composite with filler rice husk/natural bentonite ratio of 70:30and addition of 5 wt% MAPE